Processos educativos envolvidos na construção da ASSOLIMA enquanto comunidade política em Poços de Caldas - MG - Jacinto, Silvana Maria (Universidade Federal de São Carlos, 2017)
This study has the objective of understanding the educational processes that contribute to the formation of the Community Association Souza Lima (ASSOLIMA) while a political community in social coexistence terms. The issues of the present study take as a theory reference the Popular Education and Educational Philosophy of Enrique Dussel, whose concept of political community is being used. The mothodology presents ASSOLIMA foundation, characteristics, practices, and covers reflections on Dusselian terms. It also describes the educational processes that emerge from the coexistence of the group members which helped to the formation of the political community. It was used a qualitative approach and four research instruments: participant observation, field diary, semi-structured interviews, and oral memory. It was observed that the beginning of the Association happened when residents got together seeking for political ways to solve problems in common and that the innovative nature of this space was the record in public political programs regarding family agriculture. In the inter-subjective relationships among the Association members, it was noted that the practice of working together made the farmers stablish a political project. We should consider that ASSOLIMA started in accordance to Dussel concepts of institution and political community, a it started as a response to the demands of an área that searched for ways to organize a political will, resulting in a politicl community that has leadership as an obeying power, collective meetings and decisions, with common goals from living from agriculture to the commitment of reporting data and figures to the community. It is hoped that this research is able to contribute to educational studies regarding reflections about educational processes to develop coexistence social practices in rural communities. This study is also expected to cooperate with social movements, forums, institutions like Associations and rural or urban Cooperatives which intend to use educational processes that privilege social coexistence to solve problems in various situations, as a political community.
Keywords: Processos educativos; Convivência; Comunidade política; Comunidade rural; Educational processes; Coexistence; Political community; Rural community; CIENCIAS HUMANAS::EDUCACAO